Development of hybrid protein cookies with a two-phase natural preservation system: Sustainable functional food innovation for nutritional and environmental sustainability - Farhan, Muhammad Haidillah (Institute for Advanced Science, Social, and Sustainable Future (IASSSF), 2025)
Background: Global food security faces significant challenges, particularly with projected rapid population growth and limited natural resources. In an effort to support sustainable food security, this study aims to develop hybrid protein cookies that combine animal and plant proteins and implement a two-phase natural preservation system. Previous studies have shown that the use of hybrid proteins can improve the nutritional quality of food products, while natural preservation systems can reduce dependence on harmful synthetic preservatives. Methods: This study used a comprehensive literature review method to formulate optimal formulation, as well as experiments to evaluate the effectiveness of a combination of whey protein, pumpkin seed flour, and mung bean in improving the nutritional profile and shelf life of cookies. Findings: The results showed that these hybrid protein cookies have a higher protein content, a softer texture, and a shelf life up to 40% longer compared to conventional cookies. Conclusion: These findings support the importance of utilizing dairy industry waste such as whey protein, as well as local resources in improving sustainability and food security. In conclusion, this hybrid protein cookie innovation offers a new solution in creating nutritious, environmentally friendly food products and supporting local economic empowerment. Novelty/Originality of this article: The original aspect of this research is the application of a natural preservation system using mangosteen peel extract, which provides a new contribution to the development of sustainable functional food products.